Autism: in search of susceptibility genes. - Lamb, J; Parr, JR; Bailey, A; Monaco, A (2002)
Autism is a neurodevelopmental disorder of unknown etiology. There is convincing data for the involvement of genetic factors in the development of autism, and the absence of any consistent evidence for an environmental, neuroanatomical, or biochemical cause has led to an increasing number of genetic studies to determine the basis of this complex disorder. The results of recent genetic linkage and candidate gene studies are reviewed in relation to the challenge of clinical and genetic heterogeneity, and prospects for the future of genetic research in autism are considered.